Reúso de água destinada à produção agrícola - Santos, Rayane Alves de Arruda (Universidade Federal Rural do Semi-Árido, 2021)
The water scarcity scenarios and the food crisis in the Brazilian semi-arid region are factors that contribute to the use of wastewater in agriculture. This practice favors the increase of agricultural production, the availability of water for crops and the control of pollution of water bodies. The objective of this study was to conduct a literature review on the reuse of water for agricultural purposes in the Brazilian semiarid region. For this, basically this review was carried out in two stages: 1) documentary research in national and international platforms and 2) the reading, interpretation, description, ordering and systematization of the information. The results of the documentary research indicated that treated wastewater is now considered a new water supply, freeing up water resources for activities that require better quality, such as human supply; water reuse is one of the important tools for water resource management that makes it possible to live with water scarcity; there are many modalities of water reuse, among which we highlight urban reuse, environmental reuse, agricultural reuse, and industrial reuse. Particularly for the Brazilian semi-arid region, the agricultural reuse is the most relevant for mitigating the hydric scarcity and environmental problems; Brazil still does not have federal legislation that presents parameters and guidelines for the reuse of water, however some states already have their legislation at state level, for example, Ceará and Minas Gerais; the inade-quate management, the lack of treatment, and the way wastewater is applied to the soil-plant system are the factors that most contribute to human and environmental contamination when adopting agricultural reuse; and depending on the level of contamination of the reused water, there are restrictions on the type of plant to be cultivated
Keywords: Efluentes; Sustentabilidade; Gestão de água; Agricultura; Effluents; Sustainability; Water management; Agriculture; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA